Determinants of Pregnancy Complications in Indonesia (Analysis of Indonesian Health Survey 2023) - Bella Safhira; Nurmalia Ermi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Data from the Central Bureau of Statistics (2020) shows that MMR in Indonesia reached 189 deaths per 100,000 live births, which is higher than in countries in Southeast Asia such as Malaysia, Brunei, Thailand, and Vietnam. Maternal deaths are often caused by complications during pregnancy and childbirth, most of which are preventable or treatable (WHO, 2020). This study aims to identify factors that influence the occurrence of pregnancy complications in Indonesia Subjects and Method: This type of research is analytical observational with a cross-sectional study design. The target population was women aged 10-54 years who had given birth in Indonesia. The total sample of this study was 50,221 respondents. The dependent variable studied was pregnancy complications, and the independent variables were age, mother's education level, employment status, mother's region of residence, parity, multiple pregnancy, antenatal care (ANC) frequency, and ANC examination components. Data were obtained through direct interviews and the MCH book then analyzed using the Complex Sample method. Results: Maternal age (aOR= 1.23; 95% CI= 1.11 to 1.36; p<0.001), maternal education (aOR= 0.90; 95% CI= 0.81 to 0.99; p= 0.038), maternal occupation (aOR= 0.88; 95% CI= 0.80 to 0.96; p= 0.008), maternal area of residence (aOR= 0.73; 95% CI= 0.66 to 0.81; p <0.001), multiple pregnancies (aOR= 1.83; 95% CI= 1.19 to 2.80; p= 0.005), and ANC (aOR= 1.17; 95% CI= 1.06 to 1.29; p= 0.001) were statistically significantly associated with pregnancy complications. Conclusion: To reduce the risk of pregnancy complications, pregnant women are strongly advised to regularly perform ANC visits and ultrasounds according to the latest regulations and conduct pregnancy examinations according to the 10T standard. Mothers with multiple pregnancies must ensure adequate nutritional intake due to higher nutrition needs.